Inoculation of aerobic granular sludge to achieve granulation under high dissolved oxygen and the associated mechanisms. (August 2021) - Song, Xin; Sun, Shiquan; Zhou, Lean; Gao, Yang; Tang, Meiyi; Jiang, Changbo; Wan, Junli; Wu, Fangtong; Chen, Jing
Abstract: AGS technology has been studied for decades, and many successful experimental research approaches and full-scale processes have been proposed. However, a precise, comprehensive understanding of the granulation mechanism remains lacking. In this study, sequencing batch reactors were partially inoculated with (S1) or without AGS (S2) to explore aerobic granulation performance in simulative low-strength wastewater. The COD, NH4 + -N removal efficiency and SND rate were 91.61%, 92.47%, and 84%, respectively, in S1 and higher in this reactor than in S2 (86.76%, 85.21%, and 75%, respectively), indicating the superiority of partial inoculation with AGS. The ratios of P release/NaAc uptake both increased to nearly 0.250, revealing the robust capacity for phosphorus enrichment. Moreover, the increment of EPS content in S2 (31.73 mg/g MLSS) was 47% higher than that in S1 (21.54 mg/g MLSS) and was contributed mainly by PS, which increased to 30.17 mg/g MLSS (S2). These findings indicated active sludge for granulation was more sensitive to the ambient conditions, and secrete greater PS. FTIR and 3D-EEM revealed that numerous hydroxyl groups were assembled within EPS upon granulation, and humic acid-like substances first increased and then decreased over the operation, implying robust cohesion and positive microbial activities. Microbial community analysis demonstrated that Paracoccus and unclassified_Cytophagales dominated in both reactors, accounting for 29.42% and 10.87%, respectively, of the community in S1 and 26.62% and 18.54%, respectively, of the community in S2. Metabolic pathway analysis revealed enhancement of microbial metabolism, cellular processes, and signaling pathways, such as methanol oxidation, methylotrophy, and nitrite denitrification pathways.